External Imbalances in the Euro Area - Chen, Ruo (IMF Working Papers; Working Paper ;, 2012)
The paper examines the extent to which current account imbalances of euro area countries are related to intra-euro area factors and to external trade shocks. We argue that the traditional explanations for the rising imbalances are correct, but are incomplete. We uncover a large impact of declines in export competitiveness and asymmetric trade developments vis-a-vis the rest of the world -in particular vis-a-vis China, Central and Eastern Europe, and oil exporters- on the external balance of euro area debtor countries. While current account imbalances of euro area deficit countries vis-a-vis the rest of the world increased, they were financed mostly by intra-euro area capital inflows (in particular by the purchase of government and financial institutions' securities, and cross-border interbank lending) which permitted external imbalances to grow over time.